Can the freshwater bacterial communities shift to the "marine‐like" taxa?. (31st March 2014) - Zhang, Lei; Gao, Guang; Tang, Xiangming; Shao, Keqiang
<x xml:space="preserve">Abstract</x> A mesocosm experiment was used to study the response of a freshwater bacterial community to increasing salinity. Bacterial community composition in the control and saline groups was analyzed using polymerase chain reaction (PCR)‐terminal restriction fragment length polymorphism (T‐RFLP) of the 16S rRNA genes, followed by clonal sequencing of eight selected samples. Cluster analysis and phylogenetic analysis revealed that the bacterial communities in pre‐ and post‐salt addition samples were significantly different. Detailed analysis showed: (i) the existing bacterial taxa markedly declined from freshwater to hypersaline habitats, although some taxa maintain balanced growth over a small salinity range through inter‐genus changes in community structures; (ii) the addition of salt induced a clear shift in the community structure toward a striking increase in the relative abundance of the latent "marine‐like" genera (e.g., Alcanivorax and Roseovarius). The reasons may be that freshwater bacteria adapt to live in low salt concentrations and low osmotic pressure. They were not adapted to high concentrations of salt, and their acute response to increasing salinity resulted in significantly decreased numbers. However, as the salinity increases, rare members of the ever‐present community (rare or dormant bacterial taxa in the "microbial seed bank") rise to the fore, while previous dominant members drop away. This study provides direct evidence for bacterial succession from halosensitive taxa in freshwater to halotolerant ones in response to water salinization.